Influence of Peruvian Andean grain flours on the nutritional, rheological, physical, and sensory properties of sliced bread - García-Ramón, Fernando; Sotelo-Méndez, Alejandrina; Alvarez-Chancasanampa, Hermelinda; Norabuena, Edgar; Sumarriva, Liliana; Yachi, Karina; Gonzales Huamán, Teresa; Naupay Vega, Marlitt; Cornelio-Santiago, Heber P. (Frontiers in Sustainable Food Systems, 2023)
The enrichment of sliced bread with Peruvian Andean grains can affect water absorption, formation time and stability of the dough, as well as the texture, color, specific volume and acceptability of the final product. However, the nutritional and functional properties of the product can be improved. In this study, traditional (TB, 100% wheat flour) and Andean (AB, 30% wheat bran, quinoa, kiwicha, oats, barley flours, and sesame and linseed seed) bread were manufactured by the direct method. The thermomechanical properties of the doughs were evaluated using the Mixolab, as well as the proximal composition, total phenolic content, texture, color, specific volume and sensory analysis of the sliced bread. The results revealed that the AB showed higher values in the parameters of water absorption (C1), protein weakening (C2), and starch stability (C4), likewise, lower values of setback related to starch retrogradation tendency (C5-C4) were found, which are related to a longer shelf life, which could be evidenced in the sensory properties (scores ≥5 on an unstructured 10-cm long scale, with respect to the crumb color, crust, alveolar uniformity, odor, texture, taste and general acceptability). In the AB there is also evidence of an increase in protein, ash, total dietary fiber and total phenolic content in relation to TB. These results could be useful to develop healthier and better-quality bread to meet the needs of consumers.